Clinicoradiographic Features and Histopathologic Variations of Intraosseous Lipoma: Report of a Case and Review of the Literature - Saede Atarbashi-Moghadam; Ali Lotfi; Mohammad Mehdizadeh; Fazele Atarbashi-Moghadam (Hindawi Limited, 2021)
Intraosseous lipoma is a very rare lesion, and the jaw is its least common bone location. Fibrolipoma is a microscopic variant of lipoma which is characterized by a significant fibrous component intermixed with lobules of fat cells. Intraosseous fibrolipoma of the jaw is a rare lesion, and to the best of our knowledge, only two cases have been reported from 1948 in English literature. This paper presents a 39-year-old man with a chief complaint of tooth displacement in the anterior region of the mandible. Radiographic evaluation revealed a unilocular radiolucent lesion with sclerotic borders located between the left lateral incisor and canine. Histopathologic evaluation after an excisional biopsy confirmed the diagnosis of intraosseous fibrolipoma. We also reviewed the literature on this rare lesion.